2021
DOI: 10.1536/ihj.20-427
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Controlled Comparison of Optimal Medical Therapy with Percutaneous Recanalization of Chronic Total Occlusion (COMET-CTO)

Abstract: The aim of this randomized prospective study was to evaluate the quality of life (QoL) using the "Seattle Angina Questionnaire" (SAQ) in patients with chronic total occlusion (CTO) in coronary arteries treated with either percutaneous coronary intervention (PCI) or optimal medical therapy (OMT), or only with OMT.The potential benefits of recanalization of CTO by PCI have been controversial because of the scarcity of randomized controlled trials.A total of 100 patients with CTO were randomized (1:1) prospective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 27 publications
0
17
0
Order By: Relevance
“…[29][30][31][32] based differences in PCI outcomes. [33][34][35] Notably, females represent no more than 20% of patients included in cardiovascular registries and randomized trials studying the outcomes of CTO PCI. 10,25,26 Despite rigorous efforts, female enrollment in the cardiovascular trials remains an ongoing challenge, 36 possibly reflecting a component of selection bias.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[29][30][31][32] based differences in PCI outcomes. [33][34][35] Notably, females represent no more than 20% of patients included in cardiovascular registries and randomized trials studying the outcomes of CTO PCI. 10,25,26 Despite rigorous efforts, female enrollment in the cardiovascular trials remains an ongoing challenge, 36 possibly reflecting a component of selection bias.…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies have shown that women have higher rates of post procedure complications following PCI though sex differences in outcomes for CTO‐PCI are not well known 29–32 . Major randomized CTO trials such as Randomized Controlled Comparison of Optimal Medical Therapy with Percutaneous Recanalization of Chronic Total Occlusion (COMET‐CTO), A Randomized Multicentre Trial to Evaluate the Utilization of Revascularization or Optimal Medical Therapy for the Treatment of Chronic Total Coronary Occlusions (EURO‐CTO), and Drug‐Eluting Stent Implantation Versus Optimal Medical Treatment in Patients With Chronic Total Occlusion (DECISION‐CTO) which compared PCI versus medical therapy for CTO have not reported sex‐based differences in PCI outcomes 33–35 . Notably, females represent no more than 20% of patients included in cardiovascular registries and randomized trials studying the outcomes of CTO PCI 10,25,26 .…”
Section: Discussionmentioning
confidence: 99%
“…The mortality benefit consistently observed in thousands of patients enrolled in controlled registries of successful CTO recanalisation versus a failed procedure (Table 1) [55][56][57][58][59][60][61] raised hopes that this could be confirmed in randomised studies. Unfortunately, among the 1,892 patients enrolled across 6 RCTs [62][63][64][65][66][67] The upper left image describes various techniques of antegrade recanalisation, starting with the "conventional" microcatheter-assisted antegrade wire escalation (3). When the stump of the occluded vessel is not visible, IVUS guidance from a probe positioned in a side branch originating immediately proximal to the occlusion can monitor in real time the direction of the cap puncture (2).…”
Section: Indications For Cto Recanalisationmentioning
confidence: 99%
“…Symptom relief is currently the main indication for CTO PCI. 2 , 5 Several observational studies and 3 6 , 7 , 8 of 4 9 randomized‐controlled trials showed symptom improvement with CTO PCI compared with optimal medical therapy (OMT) alone. In the EuroCTO (randomized multicenter trial to compare revascularization with OMT for the treatment of chronic total coronary occlusions) trial, 396 patients were randomized to OMT versus OMT+PCI.…”
Section: Benefitsmentioning
confidence: 99%